A case of complete response to nivolumab after long-term progression-free survival with tyrosine kinase inhibitor. Issue 9 (October 2018) - Mollica, Veronica; Di Nunno, Vincenzo; Corcioni, Beniamino; Fiorentino, Michelangelo; Nobili, Elisabetta; Schiavina, Riccardo; Golfieri, Rita; Brunocilla, Eugenio; Ardizzoni, Andrea; Massari, Francesco
Abstract : Nivolumab is an effective and tolerable treatment for metastatic renal cell carcinoma, showing longer median overall survival than everolimus and achieving a good percentage of objective response, stable disease, and prolonged responses. However, very few cases have been reported in the literature of a complete response to nivolumab in the metastatic pretreated setting. Here, we report a case of complete response to nivolumab in II line following sunitinib in a metastatic clear cell renal cell carcinoma with favorable risk according to the IMDC criteria. This is also an interesting case on the use of immunotherapy following a long period of antiangiogenetic therapy, underlining the importance of the sequence of treatment to achieve the best possible outcome in terms of prolonged overall survival, progression-free survival, and objective response.